Regulação internacional de Basiléia: perspectiva co-evolutiva das regras em razão da interação entre regulador e instituição financeira - Guedes, Cristiane Maria de Moura (2015)
This study has as main objective to analyze whether the financial organizations and interacted significantly influenced the regulatory institutions producing changes or adjustments to the conditions of the banking environment due to the sharing of knowledge and information on the regulation and international prudential supervision, the Basel Accord. It is a qualitative research, justified by the complexity of the phenomenon and the multiple aspects involved which would hardly be captured by quantitative approaches. The method used is the only case study with in-depth interviews and content analysis for collection and processing of information. The theoretical lens is the institutional co-evolution, as a theory with dynamic perspective when considering that in the interactive process between organizations, institutions and the environment, the agents adapt to distinct and independent ways forward to new conditions. Changes in regulation may be attached to strategic maneuvers of financial organizations in the search for development of the environment, is innovating instruments and influencing the other participants or articulating cooperation actions. In this regard, we look at how the international regulation influenced local organizations and how these, in the process of interaction with the regulator, eventually influenced changes in the banking environment. It was observed that developments in the regulatory and supervisory spheres (preventive prudential measures) occurred before adverse scenarios of the global economy where organizations anticipated regulatory changes that would allow them leeway and greater conservatism in the face of external crises scenarios. Examples of best management practices, more dynamic governance and pricing instruments coming from the international market led to strategic changes in the organizational field, to adapt the organization to the environmental context and the strategic changes of choices that resulted in strong and influential interaction, individual and deliberate or collective response to threats and opportunities perceived, with other market organizations and the regulator through technical cooperation and exchange of knowledge, influencing strategic practices of interest to leading organizations and their stakeholders.